Correlation Analysis between Tibial Tuberosity‐Trochlear Groove Distance and Other Patellar Stability Parameters in Young and Middle‐aged Populations. Issue 8 (16th June 2022) - Qi, Yang; Liu, Jingyan; Sun, Man; Wang, Zhi
Abstract : Objective: The exact mechanism of patellofemoral instability has not been clearly clarified. The current study aims to explore the correlation between the tibial tuberosity‐trochlear groove (TT‐TG) distance and other patellar stability parameters. Methods: A total of 60 individuals aged 18 to 40 years who underwent knee computed tomography (CT) examination between September 2014 and December 2017 were retrospectively recruited. Five reference sites were selected on the femoral trochlear articular surface in every CT image. The TT‐TG distance and the trochlear groove angles (TGA) at the five reference sites were measured. The patellar ligament length (PLL), patellar length (PL), medial patellar retinaculum length (MPRL) and lateral patellar retinaculum length (LPRL) were quantitatively analyzed. The TT‐TG distances on different knee sides or in different sexes were compared. The relationships between the TT‐TG distance and TGA, PLL/PL, MPRL, and LPRL were analyzed by Spearman's method. Comparison analysis among patellar stability parameters was analyzed using ANOVA or two‐tailed Student's t test. Results: Variance analysis revealed no significant differences in the TT‐TG distances among the five positions of the femoral trochlea ( F  = 0.67, P  = 0.62) but significant differences among the five femoral TGAs at the five reference sites ( F  = 380.37, P  < 0.01). Notably, an increasing tendency of the TT‐TG distance was observed in the sexes (male, range 16.61–19.68 mm; female, range 14.37–17.38 mm) and knee sides (left knee, range 14.37–18.43 mm; right knee, range 15.80–19.68 mm). The TGA at site 1 of the femoral trochlear cartilage was the largest, with an angle of 151.97° ± 10.4°, and then gradually decreased to the smallest when the cartilage disappeared at site 5, with an angle of 92.05° ± 10.01°. Interestingly, there was a positive relationship between the TT‐TG distance at site 1 and TGA in the right knees of males ( r  = 0.490, P  = 0.033) as well as LPRL in the left knees of males ( r  = −0.420; P  = 0.046). There were no correlations between the TT‐TG distance and the other patellar stability parameters, including TGA, PLL/PL, MPRL, and LPRL. Conclusion: Among young and middle‐aged populations, patella surgeries should be carefully determined based on the comprehensive consideration of these patellar stability parameters rather than the TT‐TG distance alone. Differences in sex and knee side should also be considered. Abstract : The TT‐TG distance, TGA, Insall–Salvati ratio (PLL/PL), MPRL, LPRL were independent of each other, and no correlations among them were observed. PL, Patella length; PLL, Patella ligament length; TT‐TG, Tibial tuberosity‐trochlear groove distance; TGA, Trochlear groove angles; MPRL, Medial patellar retinaculum length; LPRL, Lateral patellar retinaculum length;